Towards the genetic basis of cerebral venous thrombosis—the BEAST Consortium: a study protocol. Issue 11 (22nd November 2016) - Cotlarciuc, Ioana; Marjot, Thomas; Khan, Muhammad S; Hiltunen, Sini; Haapaniemi, Elena; Metso, Tiina M; Putaala, Jukka; Zuurbier, Susanna M; Brouwer, Matthijs C; Passamonti, Serena M; Bucciarelli, Paolo; Pappalardo, Emanuela; et al.
Abstract : Introduction: Cerebral venous thrombosis (CVT) is a rare cerebrovascular condition accounting for <1% of all stroke cases and mainly affects young adults. Its genetic aetiology is not clearly elucidated. Methods and analysis: To better understand the genetic basis of CVT, we have established an international biobank of CVT cases, Biorepository to Establish the Aetiology of Sinovenous Thrombosis (BEAST) which aims to recruit highly phenotyped cases initially of European descent and later from other populations. To date we have recruited 745 CVT cases from 12 research centres. As an initial step, the consortium plans to undertake a genome-wide association analysis of CVT using the Illumina Infinium HumanCoreExome BeadChip to assess the association and impact of common and low-frequency genetic variants on CVT risk by using a case–control study design. Replication will be performed to confirm putative findings. Furthermore, we aim to identify interactions of genetic variants with several environmental and comorbidity factors which will likely contribute to improve the understanding of the biological mechanisms underlying this complex disease. Ethics and dissemination: BEAST meets all ethical standards set by local institutional review boards for each of the participating sites. The research outcomes will be published in international peer-reviewed open-access journals with high impact and visibility. The results will be presented at national and international meetings to highlight the contributions into improving the understanding of the mechanisms underlying this uncommon but important disease. This international DNA repository will become an important resource for investigators in the field of haematological and vascular disorders.